From information to action: modelling social and cognitive factors in health decisions - Jiadong Yu; D. A. Bekerian (BMC Public Health)
Abstract Background This study examines the social and cognitive factors influencing health decisions to adopt protective behaviors in a U.S. sample. A theoretical framework was developed, incorporating key variables such as perceived severity, perceived vulnerability, use of formal and informal health information, conspiracy beliefs, and political ideology. The protective behaviors studied included mask-wearing and vaccination intentions. Methods This study employed a cross-sectional design to explore how cognitive appraisals and socio-political factors influence health decisions. Data were collected from 742 U.S.-based participants via Amazon Mechanical Turk (MTurk) between January 28–30, 2023. Results Perceived vulnerability and perceived severity had distinct effects on information source preferences. Reliance on formal sources positively correlated with compliance behaviors such as mask-wearing and vaccination, while perceived severity strongly predicted mask adherence. In contrast, perceived vulnerability was associated with conspiracy beliefs and informal information use. Notably, fear of COVID-19 did not significantly influence health behaviors. Instead, political ideology and conspiracy beliefs played a more dominant role, emphasizing the importance of integrating socio-political factors into traditional health behavior models. Conclusions Understanding the complex interplay of cognitive and socio-political factors is crucial for developing effective public health strategies to enhance compliance with health guidelines during the COVID-19 pandemic and future crises.